MAKNA LABA BAGI PERSPEKTIF PETANI - Kiky Zulkifli (RISTANSI: Riset Akuntansi, 2022)
This study intends to find out how the meaning of profit for farmers. Through this research, it is expected to find a suitable concept in applying accounting knowledge in the agribusiness sector. The type of research used in this study is a qualitative research. This qualitative approach reveals a unique meaning of accounting as understood by farmers. Therefore, to be able to carry out deepening activities on an entity, namely by using phenomenology. Based on the results of research conducted, farmers actually already understand the importance of an accounting practice in determining the profit and loss of their business activities. However, farmers have difficulty in compiling a good and correct financial report so that they never know how much profit for sure in each planting period. This is due to the lack of knowledge of accounting practices and the low level of education of farmers in carrying out the process of recording financial statements properly and correctly according to applicable standards. The recording carried out by farmers is only a "simple" record, namely cash in and cash out for reminders from farmers.